Sustained Immune Complex-Mediated Reduction in CD16 Expression after Vaccination Regulates NK Cell Function - Goodier, Martin R.; Lusa, Chiara; Sherratt, Sam; Rodriguez-Galan, Ana; Behrens, Ron; Riley, Eleanor M. (Frontiers in Immunology, 2016)
Cross-linking of FcγRIII (CD16) by immune complexes induces antibody dependent cellular cytotoxicity (ADCC) by natural killer (NK) cells, contributing to control of intracellular pathogens; this pathway can also be targeted for immunotherapy of cancerous or otherwise diseased cells. However, down-regulation of CD16 expression on activated NK cells may limit or regulate this response. Here, we report sustained downregulation of CD16 expression on NK cells in vivo after intramuscular (but not intranasal) influenza vaccination. CD16 downregulation persisted for at least 12 weeks after vaccination and was associated with robust enhancement of influenza-specific plasma antibodies after intramuscular (but not intranasal) vaccination. This effect could be emulated in vitro by co-culture of NK cells with influenza antigen and immune serum and, consistent with the sustained effects after vaccination, only very limited recovery of CD16 expression was observed during long term in vitro culture of immune complex-treated cells. CD16 downregulation was most marked among normally CD16high CD57+ NK cells, irrespective of NKG2C expression, and was strongly positively associated with degranulation (surface CD107a expression). CD16 downregulation was partially reversed by inhibition of ADAM17 matrix metalloprotease, leading to a sustained increase in both CD107a and CD25(IL-2R) expression. Both the degranulation and CD25 responses of CD57+ NK cells were uniquely dependent on TIV-specific IgG. These data support a role for CD16 in early activation of NK cells after vaccination and for CD16 down regulation as a means to modulate NK cell responses and maintain immune homeostasis of both antibody and T cell-dependent pathways.